Diabetes in pregnancy: the effect of good diabetic control on outcome. (7th June 2011) - Szubert, W; Oswald, S E; Dick, A; Love, C D B
Abstract : Pre-existing diabetes is associated with risks to women and their babies and the prevalence is continuously increasing, as identified in the recent CEMACH review. This audit aimed to review antenatal care and pregnancy outcomes in women with Type 1 and 2 diabetes, and to quantify the effect of good diabetic control on pregnancy outcome. A retrospective review took place of Type 1, Type 2 and MODY pregnancies from May 2005 to December 2009 at the Simpson Centre for Reproductive Health, Edinburgh. 150 pregnancies were analysed: 105 Type 1, 41 Type 2 and 4 MODY. 31% of women received documented preconception advice. Diabetic control improved over the course of pregnancy; 37% had HbA1c>7.5% at booking, decreasing to only 15% by the third trimester. 26% delivered preterm (<37 weeks). 23.5% of pregnancies were complicated by hypertension. 40% achieved vaginal delivery and 60% had caesarean sections (20% elective and 40% emergency). 30% of babies required admission to neonatal unit (NNU) and 24% of pregnancies had macrosomia. A normalised third trimester HbA1c (<6.1%), reduced the incidence of preterm deliveries (p=0.007) and increased likelihood of vaginal delivery from 40% across all diabetic pregnancies to 59% (p=0.020). In addition, good control in the third trimester significantly reduced the incidence of NNU admission (p=0.027). This highlights a UK wide problem of poor attendance for preconception care, especially for those with Type 2 diabetes. However, intensive multidisciplinary antenatal care improves the outcome of diabetic pregnancies. Effort should be focused on good diabetic control, especially in the third trimester.